Effects of acute androstenedione supplementation on testosterone levels in older men. (2nd July 2016) - Judge, Lawrence W.; Bellar, David M.; Hoover, Donald L.; Biggs, Douglas; Leitzelar, Brianna N.; Craig, Bruce W.
Abstract: The purpose of the study was to examine the effects of acute androstenedione supplementation on hormone levels in older men at rest and during exercise. Men ( n = 11) between the ages of 58 and 69 were divided into an experimental ( n = 6; 62.33 ± 2.57 y) and control ( n = 5; 60.2 ± 1.02 y) groups. Each participant received an oral 300 mg dose of either androstenedione (experimental) or a cellulose placebo (control) for 7 d. Pre- and post-supplementation participants completed two separate, 20-min strength tasks consisting of leg extension and leg curls at different percentages of their 10-RM. Researchers collected blood samples pre-, during, and post-exercise. Blood samples were analyzed for testosterone, androstenedione, and estradiol levels. The researchers found a significant difference between pre- (4.36 ± 56 ng/mL) and post- (5.51 ± 0.35 ng/mL) testosterone levels, as well as pre- (0.88 ± 0.20) and post- (7.46 ± 1.25) androstenedione levels, but no significant differences between pre- and post-estradiol levels for either group. It appears that short-term androstenedione supplementation augmented acute testosterone responses to resistance exercise in older men. However, further study of this supplement is needed to determine any potential it may have in mitigating andropause.